2022
DOI: 10.3390/biomedicines10030544
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hub and Spoke Regions in Theory of Mind in Early Alzheimer’s Disease and Frontotemporal Dementia

Abstract: Theory of mind (ToM, the ability to attribute mental states to others) deficit is a frequent finding in neurodegenerative conditions, mediated by a diffuse brain network confirmed by 18F-FDG-PET and MR imaging, involving frontal, temporal and parietal areas. However, the role of hubs and spokes network regions in ToM performance, and their respective damage, is still unclear. To study this mechanism, we combined ToM testing with brain 18F-FDG-PET imaging in 25 subjects with mild cognitive impairment due to Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…In the end, also the most recent study of the present review (Orso et al, 2022 ), agrees with the previous studies. In fact, it is reported that MCI-AD patients ( n = 25) showed a poorer performance in the RMET compared to HC ( n = 40).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the end, also the most recent study of the present review (Orso et al, 2022 ), agrees with the previous studies. In fact, it is reported that MCI-AD patients ( n = 25) showed a poorer performance in the RMET compared to HC ( n = 40).…”
Section: Resultssupporting
confidence: 93%
“…Different research showed that TOM can be impaired in several neurodegenerative disorders, such as in Alzheimer's Disease (as reported by Morese et al, 2018;Kessels et al, 2021;Morese and Palermo, 2022), Parkinson's Disease (Rossetto et al, 2018;Adenzato et al, 2019;Morese and Palermo, 2020), Frontotemporal Dementia-behavioral variant (Adenzato et al, 2010;Poletti et al, 2012;Orso et al, 2022), but also in cognitive disorders without dementia, such as Mild Cognitive Impairment (MCI). In this regard, several studies reported lower performance in many TOM tasks in MCI patients, compared to healthy populations (Baglio et al, 2012;Poletti and Bonuccelli, 2013;Moreau et al, 2015;Adenzato et al, 2019;Orso et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The age-related impairments in the ability to process contextual information and in the regulation of responses to threat are related to structural and physiological alterations in the PFC and medial temporal lobe [ 177 ]. Positron emission tomography with 2-deoxy-2-[fluorine-18]fluoro-D-glucose has shown the deficit of hubs in the theory of mind network in patients with mild cognitive impairment due to AD [ 178 ]. Brain autopsy and imaging studies reveal the atrophy of the brain including the frontal, temporal, parietal, entorhinal cortices, amygdala, and hippocampus [ 179 ].…”
Section: Diseases Linked To Mitochondrial Dysfunctionmentioning
confidence: 99%
“…There are also studies about risk factors, pathogenesis, and structural and functional changes associated with neurodegeneration in AD [32][33][34], the genetic, clinical, and biochemical data of individual patients [35], searching for peripheral biomarkers in neurodegenerative diseases [36] and gut microbiota regulation and their implication in the development of neurodegenerative disease [37,38]. In [39], the pathophysiological basis and biomarkers of AD pathology, and molecular signs of neural inflammation in neurodegenerative diseases are investigated. In [39,40], the roles of hub and spoke regions in theory of mind in early AD and frontotemporal dementia are studied.…”
Section: Introductionmentioning
confidence: 99%
“…In [39], the pathophysiological basis and biomarkers of AD pathology, and molecular signs of neural inflammation in neurodegenerative diseases are investigated. In [39,40], the roles of hub and spoke regions in theory of mind in early AD and frontotemporal dementia are studied. In [40], the etiological factors behind neurodegenerative disease are explored.…”
Section: Introductionmentioning
confidence: 99%